Analisis Bauran Pemasaran Susu Kambing Etawa Pada Usaha Peternakan Tuahta Farm Di Desa Paya Bujok Seuleumak, Kecamatan Langsa Baro, Kota Langsa - Puspita, Hilda; Gustiana, Cut; Basriwijaya, K.M.Z. (Jurnal Penelitian Agrisamudra, 2024)
This study was conducted with the aim of analyzing the marketing mix of etawa goat milk in the Tuahta Farm livestock business in Paya Bujok Seuleumak Village, Langsa Baro District, Langsa City. Primary data were obtained by observation, interviews, and direct questionnaires with respondents. In this study, the respondents was the owner of Tuahta Farm in Paya Bujok Seuleumak Village, Langsa Baro District, Langsa City. The sampling technique in this study uses the case study method. The data analysis used was descriptive qualitative. The results showed that: 1) The product mix, for a variety of products is less varied, for design is still the same as product design in general, 2) Price mix, payment methods are less diverse. 3) Promotion mix, promotional activities have not gone well, you should make a clear advertising strategy. 4) Distribution mix, already good compared to product mix, price mix, and promotion mix.